Physiological Response of Mentik Wangi Rice (Oryza sativa L.) to Zinc oxide Nanoparticles Under Drought Stress - Abdul Zaki; Yovi Avianto; Henra Henra; Rina Puji Lestari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Mentik wangi rice (Oryza sativa L.) is a local aromatic Indonesian variety known for its superior grain quality but susceptible to drought Stress. 2Zinc Oxide Nanoparticles (ZnO-NPs) have been widely investigated as nano-fertilizers to improve plant physiological performance under abiotic stress; however, information regarding their effects on the local aromatic rice cultivar Mentik Wangi remains limited. This study aimed to evaluate the physiological responses of Mentik Wangi rice to ZnO-NPs application under drought stress and to identify the most effective ZnO-NPs concentration for each physiological parameter. The experiment was arranged in a factorial Completely Randomized Design with two water regimes (50% and 100% field capacity) and six ZnO-NPs concentrations (0, 0.75, 1.50, 2.25, 3.00, and 3.75 ppm). Data were analyzed using two-way analysis of variance followed by Duncan's Multiple Range Test at the 5% significance level. Under drought stress, ZnO-NPs at 2.25 ppm produced the highest photosynthetic rate (0.79 µmol CO₂ m⁻² s⁻¹) and improved membrane stability index, whereas 1.50 ppm resulted in the lowest transpiration rate (0.016 mmol H₂O m⁻² s⁻¹) and the highest proline accumulation. Chlorophyll content also increased under normal conditions following the application of 2.25 ppm ZnO-NPs. In contrast, ZnO-NPs did not significantly affect ascorbic acid content or relative water content. These findings indicate that the physiological response of Mentik Wangi rice to ZnO-NPs depends on the parameter evaluated, with 2.25 ppm and 1.50 ppm producing the most favorable responses for different physiological traits under the conditions of this study.